Compensation of Workers in the Creative Industries in Thailand - Setboonsrung, Yuvaluck (Journal of Applied Economics and Management Strategy, 2025)
This research aimed to study compensation of workers in the creative industries in Thailand. This research used demographic-related data collected from the National Statistical Office (NSO) in the Labor Force Survey from 2012–2022, totaling 11 years with 10,711 observations. Descriptive statistics and regression analysis were used to describe the characteristics of labor compensation in the creative industry. The majority of creative industry workers (98 percent) were private employees, worked in the Creative Originals group, lived in the municipal area, had a primary education level, were married and were female. In the part of studying the factors related to labor compensation in the creative industry, this study applied Mincer’s (1974) wage model It was found that factors that affect labor compensation in creative industries in Thailand were gender, marital status, household head status, educational level, work experience, minimum wage rate, provincial GDP per capita, provincial consumer price index, and urbanization. In addition, it was found that only those working in the Creative Goods/Products, Creative Content/Media, and Creative Originals groups had average labor compensation that is 6.3 percent, 5.1 percent, and 2 percent higher than those working in other creative group, respectively. By investing in education, developing the skills necessary for workers in the creative industries was also essential for the country’s economic development.